Motivational factors and leadership in commercial chains in Sinaloa. A theoretical framework - López López, José de Jesús; Beltran Lugo, Lizbeth; Montoya Leyva, Miguel Angel; Castro Rivera, Radames; Peinado Guevara, Jesús Alberto (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The objectives of this paper are: To analyse the influence of motivation and leadership by management on employee performance. To identify the management tools or strategies used by the administration that have the greatest influence on motivating and encouraging better performance in the duties of employees. The qualitative documentary study allowed for a bibliographical review of the background of motivation and leadership. Theoretical approaches are organised with information from research results, which have provided answers to the main questions on the subject recently. As a contribution to the knowledge on the analysis of the influence of motivation and leadership by managers on the performance of employees, it is concluded that motivation and leadership meet the conditions of complex issues, where a variety of internal factors are permanently related to external factors in a relationship and subordination. It is also significant that an employee is encouraged and a good working atmosphere and good working relationship is managed, and under these conditions, stress is reduced, and this keeps the employee satisfied. Therefore, harmonious working methods are required, where there is reciprocity and tolerance, where the leader knows how to manage the way of working accurately, and implements measures that are favourable for the whole organisation.